Effect of acaricide and insecticide mixtures against citrus leprosis vector, Brevipalpus yothersi, under laboratory and field conditions - Vechia, Jaqueline F. Della [UNESP]; Andrade, Daniel J. de [UNESP] (Elsevier, 2022)
The intense spraying of insecticides has negatively affected the management of the leprosis vector mite, Brevipalpus yothersi, requiring additional acaricide applications. Therefore, the main objective of this study was to assess the toxicity of the acaricide spirodiclofen and several insecticides, alone or combined, on different developmental stages of B. yothersi in the laboratory and field. Additionally, the concentration of the active ingredient spirodiclofen was quantified in the spray solutions. The efficacy of spirodiclofen on the eggs and adults of B. yothersi was drastically reduced when spirodiclofen was sprayed in a mixture with cypermethrin, phosmet, or imidacloprid, with 65.4%, 57.2%, and 53.4% of reduction in eggs mortality, and 24.4%, 57.7%, and 17.6% of reduction in adult mortality, respectively. In the field, the addition of insecticides to the spirodiclofen solution decreased the period for reinfestation of the mites by the acaricide from 127 days with spirodiclofen alone to 42 (cypermethrin), 43 (phosmet), and 52 (imidacloprid) days. There was no significant reduction in the spirodiclofen concentration when mixed with insecticides. Our results indicate that the insecticides cypermethrin, phosmet, and imidacloprid antagonize the efficacy of spirodiclofen on eggs and adults of B. yothersi.
Keywords: Antagonism; Citrus; Efficacy; Period for reinfestation; Tank mixture